Effects of decentralization on the functionality of health facility governing committees in lower and middle-income countries: a systematic literature review - Anosisye M Kesale; Christopher Mahonge; Mikidadi Muhanga (Taylor & Francis Group, 2022)
Background Health facility governing committees (HFGCs) were established by lower and middle-income countries (LMICs) to facilitate community participation at the primary facility level to improve health system performance. However, empirical evidence on their effects under decentralization reform on the functionality of HFGCs is scant and inconclusive. Objective This article reviews the effects of decentralization on the functionality of HFGCs in LMICs. Methods A systematic literature review was conducted using various search engines to obtain a total number of 24 relevant articles from 14 countries published between 2000 and 2020. Inclusion criteria include studies must be on community health committees, carried out under decentralization, HFGCs operating at the individual facility, effects of HFGCs on health performance or health outcomes and peer-reviewed empirical studies conducted in LMICs. Results The study has found varied functionality of HFGCs under a decentralization context. The study has found many HFGCs to have very low functionality, while a few HFGCs in other LMICs countries are performing very well. The context and decentralization type, members' awareness of their roles, membership allowance and availability of resource to the facility in which HFGCs operate to produce the desired outcomes play a significant role in facilitating/limiting them to effectively carry out the devolved duties and responsibilities. Conclusion Fiscal decentralization has largely been seen as important in making health committees more autonomous, even though it does not guarantee the performance of HFGCs.